Analisis Hukum Undang-Undang Nomor 8 Tahun 2011 Pasal 10 Ayat 1 Tentang Putusan Mahkamah Konstitusi Yang Bersifat Final: Putusan, Final, Mahkamah Konstitusi - Abi Sugara; Arif Wibowo (Jurnal Penelitian Multidisiplin, 2022)
The constitutional court is one of the judicial power institutions that has the authority to try cases and also resolve cases from the first level to the last level, in exercising judicial power a decision if it has been issued by the constitutional court then the decision is final and also binding in the sense of the word if a the decision has been issued by the constitutional court, the decision is no longer legal, that's why the law gives four powers to the constitutional court to become one of the institutions that can uphold the law and also justice in Indonesia and the four authorities are: 1) examine the 1945 Constitution 2) decide on a dispute over authority between state institutions whose authority has been granted by the state based on the 1945 Constitution 3) decide on the dissolution of political parties 4) decide on disputes over election results.